Adhesion promotion and corrosion resistance of mixed phosphonic acid monolayers on AA 2024 - Ruhm, Lukas; Löseke, Jannik; Vieth, Pascal; Prüßner, Tim; Grundmeier, Guido (Applied Surface Science)

Tuning the Permeation Properties of Poly(1‐trimethylsilyl‐1‐propyne) by Vapor Phase Infiltration Using Trimethylaluminum - Jenderny, Jonathan; Boysen, Nils; Rubner, Jens; Zysk, Frederik; Preischel, Florian; de los Arcos de Pedro, Maria Teresa; Damerla, Varun Raj; Kostka, Aleksander; Franke, Jonas; Dahlmann, Rainer; Kühne, Thomas D.; Wessling, Matthias; et al. (Advanced Materials Interfaces)
Abstract Vapor phase infiltration (VPI) has emerged as a promising tool for fabrication of novel hybrid materials. In the field of polymeric gas separation membranes, a beneficial impact on stability and membrane performance is known for several polymers with differing functional groups. This study for the first time investigates VPI of trimethylaluminum (TMA) into poly(1‐trimethylsilyl‐1‐propyne) (PTMSP), featuring a carbon–carbon double bond as functional group. Saturation of the precursor inside the polymer is already attained after 60 s infiltration time leading to significant densification of the material. Depth profiling proves accumulation of aluminum in the polymer itself, but a significantly increased accumulation is visible in the gradient layer between polymer and SiO 2 substrate. A reaction pathway is proposed and supplemented by density‐functional theory (DFT) calculations. Infrared spectra derived from both experiments and simulation support the presented reaction pathway. In terms of permeance, a favorable impact on selectivity is observed for infiltration times up to 1 s. Longer infiltration times yield greatly reduced permeance values close or even below the detection limit of the measurement device. The present results of this study set a strong basis for the application of VPI on polymers for gas‐barrier and membrane applications in the future.

Interactions of polyvinyl acetate dispersions with nanostructured superhydrophilic and superhydrophobic Ti6Al4V alloy surfaces - Neßlinger, Vanessa; Atlanov, Jan; Grundmeier, Guido (Discover Applied Sciences)
Abstract Nanostructured bilayer thin films with superhydrophobic and superhydrophilic surfaces were prepared using Ti6Al4V alloy substrates which allowed for the comparative analysis of polyvinyl acetate (PVAc) particle adsorption as a function of the interface structure. The PVAc particles were obtained from emulsion polymerization of vinyl acetate. A superhydrophilic TiO 2 nanofiber-based 3D network was created on the Ti6Al4V alloy substrate by application of a hydrothermal method. Subsequent UV-grafting of ultra-thin polydimethylsiloxane (PDMS) layers resulted in a superhydrophobic surface. The modification steps were followed via Diffuse Reflectance Infrared Fourier Transform Spectroscopy, X-ray Photoelectron Spectroscopy, Field Emission-Scanning Electron Microscopy, contact angle and Electrochemical Impedance Spectroscopy. A mechanism for the adsorption of PVAc at the two electrolyte/substrate interfaces could be revealed.

X-ray Absorption Spectroscopy Reveals Mechanisms of Calcium and Silicon Fouling on Reverse Osmosis Membranes Used in Wastewater Reclamation - Niemann, Valerie A.; Huck, Marten; Steinrück, Hans-Georg; Toney, Michael F.; Tarpeh, William A.; Bone, Sharon E. (ACS ES&T Water)
Keywords: Water Science and Technology; Environmental Chemistry; Chemistry (miscellaneous); Chemical Engineering (miscellaneous)

Thermophoretic Analysis of Biomolecules across the Nanoscales in Self-Assembled Polymeric Matrices - Liu, Ping; Schumann, Nils; Abele, Fabian; Ren, Fazheng; Hanke, Marcel; Xin, Yang; Hartmann, Andreas; Schlierf, Michael; Keller, Adrian; Lin, Weilin; Zhang, Yixin (ACS Applied Nano Materials)
Keywords: General Materials Science

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Heterogeneous Structural Evolution of In–Zn–O Thin Films during Annealing - Moffitt, Stephanie L.; Cao, Chuntian; Van Hest, Maikel F. A. M.; Schelhas, Laura T.; Steinrück, Hans-Georg; Toney, Michael F. (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Electropolymerization of acrylic acid on steel for enhanced joining by plastic deformation - Duderija, B.; Sahin, F.; Meinderink, D.; Calderón-Gómez, J.C.; Schmidt, H.C.; Homberg, W.; Grundmeier, G.; González-Orive, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Creating water-in-salt-like environment using coordinating anions in non-concentrated aqueous electrolytes for efficient Zn batteries - Gomez Vazquez, Dario; Pollard, Travis P.; Mars, Julian; Yoo, Ji Mun; Steinrück, Hans-Georg; Bone, Sharon E.; Safonova, Olga V.; Toney, Michael F.; Borodin, Oleg; Lukatskaya, Maria R. (Energy & Environmental Science)
By using coordinating anions such as acetate, a water-in-salt-like coordination environment of Zn ions is achieved in relatively dilute conditions, leading to prolonged and efficient cycling of zinc metal anodes.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

The nature of dynamic local order in CH3NH3PbI3 and CH3NH3PbBr3 - Weadock, Nicholas J.; Sterling, Tyler C.; Vigil, Julian A.; Gold-Parker, Aryeh; Smith, Ian C.; Ahammed, Ballal; Krogstad, Matthew J.; Ye, Feng; Voneshen, David; Gehring, Peter M.; Rappe, Andrew M.; Steinrück, Hans-Georg; et al. (Joule)
Keywords: General Energy

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

High-speed AFM studies of macromolecular dynamics at solid/liquid interfaces - Keller, Adrian; Grundmeier, Guido (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

Cation-dependent assembly of hexagonal DNA origami lattices on SiO2 surfaces - Pothineni, Bhanu Kiran; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami nanostructures have emerged as functional materials for applications in various areas of science and technology. In particular, the transfer of the DNA origami shape into inorganic materials using...
Keywords: General Materials Science